Do MRI findings identify patients with chronic low back pain and Modic changes who respond best to rest or exercise: A subgroup analysis of a randomised controlled trial - Jensen, R.; Kent, Peter; Hancock, M. (BioMed Central Ltd., 2015)
Background: No previous clinical trials have investigated MRI findings as effect modifiers for conservative treatment of low back pain. This hypothesis-setting study investigated if MRI findings modified response to rest compared with exercise in patients with chronic low back pain and Modic changes. Methods: This study is a secondary analysis of a randomised controlled trial comparing rest with exercise. Patients were recruited from a specialised outpatient spine clinic and included in a clinical trial if they had chronic low back pain and an MRI showing Modic changes. All patients received conservative treatment while participating in the trial. Five baseline MRI findings were investigated as effect modifiers: Modic changes Type 1 (any size), large Modic changes (any type), large Modic changes Type 1, severe disc degeneration and large disc herniation. The outcome measure was change in low back pain intensity measured on a 0-10 point numerical rating scale at 14-month follow-up (n = 96). An interaction = 1.0 point (0-10 scale) between treatment group and MRI findings in linear regression was considered clinically important. Results: The interactions for Modic Type 1, with large Modic changes or with large Modic changes Type 1 were all potentially important in size (-0.99 (95% CI -3.28 to 1.29), -1.49 (-3.73 to 0.75), -1.49 (-3.57 to 0.58), respectively) but the direction of the effect was the opposite to what we had hypothesized-that people with these findings would benefit more from rest than from exercise. The interactions for severe disc degeneration (0.74 (-1.40 to 2.88)) and large disc herniation (-0.92 (3.15 to 1.31)) were less than the 1.0-point threshold for clinical importance. As expected, because of the lack of statistical power, no interaction term for any of the MRI findings was statistically significant. Conclusions: Three of the five MRI predictors showed potentially important effect modification, although the direction of the effect was surprising and confidence intervals were wide so very cautious interpretation is required. Further studies with adequate power are warranted to study these and additional MRI findings as potential effect modifiers for common interventions.